Adsorption of Chelerythrine from Toddalia asiatica (L.) Lam. by ZSM-5 - Yunlong Liu; Jie Guo; Zhuobing Xiao; Dazhao Peng; Ke Song (Advances in Polymer Technology)
Separation and purification of active components from biomass by inorganic materials during the pretreatment process of hydrothermal conversion are studied in this work. The batch experiment results show that an initial solution pH of 6 favors chelerythrine adsorption, and the optimum adsorbent dosage is 2.0 g. The adsorption mechanism of ZSM-5 for chelerythrine is investigated by adsorption kinetics, isotherm adsorption models, and thermodynamics analysis. The results show that the kinetics data fit the pseudo-second-order model well (R2 = 0.9991), and the intraparticle diffusion model has 3 diffusion stages, preliminarily indicating that chemisorption plays a major role in the adsorption process, and the sorption mechanism includes intraparticle, external, and boundary diffusion. The adsorption isotherms agree well with the Langmuir model, indicating the occurrence of monolayer molecular adsorption during the adsorption process. Meanwhile, the maximum adsorption capacity is 2.327, 2.072, and 1.877 mg/g at different temperatures (288 K, 298 K, and 308 K), respectively. The thermodynamic data demonstrate that the adsorption process is exothermic and spontaneous in nature. These observed results clearly confirm that ZSM-5 has potential superior properties for the enrichment and purification of alkaloids during the pretreatment of biomass.